Understanding emotions - Anders, S. (Silke); Ende, G. (Gabriele); Junghofer, Markus; Kissler, Johanna; Wildgruber, D. (Dirk) (Progress in brain research ;, 2006)
Emotions shape all aspects of our thinking and behavior, particularly when we communicate with others. How does our brain respond to emotions conveyed by picture media, human faces, voices, and written language? How do we integrate this information in social interaction? What goes wrong in the brains of people suffering from emotional disorders? This book reviews modern neuroscientific and psychological research providing answers to these questions. In this volume, leading researchers give comprehensive overviews of the current knowledge on different aspects of emotional perception and the und.